Analyzing the relationship between lean manufacturing and operational performance of the automotive sector's companies in Brazil (Revista de Administração, 2013)
Arguments that lean manufacturing can positively relate with the operational performance of companies have been spreading the literature since the 1990s. However, there is a theoretical and empirical gap on this issue that needs further empirical evidence to validate or refute these arguments to the Brazilian reality. Hence, this research aims to, empirically, verify if the lean manufacturing positively influences the performance of the operations of companies in the Brazilian automotive industry, focusing on the segment of automotive parts and components. Methodologically, we carried out a survey of 75 companies in the mentioned sector. The data were analyzed using Structural Equation Modeling, a second-generation multivariate analysis. The main results of this research are: in fact, lean manufacturing positively affects the operational performance of the studied companies, validating the main hypothesis stated in this article, but this relation is just considered weak, although positive; all lean manufacturing practices analyzed were encountered in the reality, especially for the variable "continuous improvement", with the highest average and the correlation between the adoption of Kanban and Just in Time; the operational performance construct has some practices/measures identified by the literature, which have not been validated by the studied sector, as innovation (new products) and quality.